A Return to Wage Discrimination: Pay Equity Losses Through the Privatization of Health Care - Cohen, Marjorie Griffin; Cohen, Marcy. (Canadian Centre for Policy Alternatives, BC Office, 2004)
Privatization has eliminated 30 years of pay equity gains and has put BC at the bottom of the barrel nationally when it comes to wages and benefits for women working in health support occupations. This is the central finding of a study released today by the Canadian Centre for Policy Alternatives. It documents the dramatic reversal of pay equity resulting from the provincial government's push to contract out hospital support services (cleaners, care aids and laundry, food service and clerical workers). "Bill 29 has turned the clock back thirty years on fair wages for women in health support occupations," says co-author Marjorie Griffin Cohen, a CCPA research associate and Chair of SFU's Women's Studies Department. -- CCPA news release, April 21, 2004

Climate Change and Labour in the Energy Sector - Cohen, Marjorie Griffin; Calvert, John (Climate@Work, 2013)
[Analyzes] the impact of both climate change and climate policy on employment in the energy sector. --Editor's introduction
Keywords: Canada. Climatic changes; Climatic changes; Economic aspects; Economic aspects. Climatic changes; Government policy